The Experimental study of safety and efficacy in using Soyeom Pharmacopuncture solution as eyedrops - Eun-Kyo Kang; Hyung-sik Seo (Korean Pharmacopuncture Institute, 2009)
Objective : This experimental study was performed to investigate the safety of Soyeom Pharmacopunture solution manufactured by extraction of alcohol and water. To identify the use of it as eyedrops, the eye irritation test of rabbits and antibacterial test of Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Aspergillus niger, Fusarium oxysporum, and Candida albicans was performed. Methods : 1. The eye irritation test of this material was performed according to the Regulation of Korea Food & Drug Administration(2005. 10. 21, KFDA 2005-60). After Soyeom pharmacopuncture solution was administered in the left eye of the rabbits, eye irritation of the cornea, iris and conjunctiva was observed at 1, 2, 3, 4 & 7day. 2. After administering Soyeom Pharmacopuncture solution on bacterial species (Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Aspergillus niger, Fusarium oxysporum, Candida albicans) which cause Keratitis, MIC(Minimum Inhibition Concentration) and the size of inhibition zone were measured. Anti-bacterial potency was also measured using the size of inhibition zone. Results : 1. After Soyeom pharmacopuncture solution was administered in the left eye of the rabbits, it was found that none of nine rabbits have abnormal signs and weight changes. 2. After Soyeom pharmacopuncture solution was medicated in the left eye of the rabbits, no eye irritation of the cornea, iris and conjunctiva was observed at 1, 2, 3, 4 & 7day. 3. There was no response to MIC on bacterial species (Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Aspergillus niger, Fusarium oxysporum, Candida albicans) after Soyeom pharmacopuncture solution was medicated. Conclusions : The present study suggests that Soyeom pharmacopuncture solution is a non-toxic and non-irritant medicine, which does not cause eye irritation in rabbits, but dosen't have anti-bacterial effects on bacterial species which cause Keratitis. These study result recommends that more research on other herbal medicines of eye drop for Keratitis are required.